Stochastic parameter regression models - Newbold, Paul. (Quantitative applications in the social sciences ;, 1985)
This introduction to stochastic parameter regression models is more advanced and technically difficult than other papers in this series. These models allow relationships to vary through time, without forcing the analyst to specify and analyze the causes of the time-varying relationships.